2017
DOI: 10.1002/14651858.cd012767
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative restrictive versus goal-directed fluid therapy for adults undergoing major non-cardiac surgery

Abstract: Perioperative restrictive versus goal-directed fluid therapy for adults undergoing major non-cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…However, in our study, we found no statistically differences in the postoperative AKI between the CFT group and the GDFT group. Therefore, the intraoperative goal-directed fluid therapy appeared to be at lower risk of postoperative AKI than the restrictive regimen, which deserves more larger, higher-quality RCTs to further study [37].…”
Section: Discussionmentioning
confidence: 97%
“…However, in our study, we found no statistically differences in the postoperative AKI between the CFT group and the GDFT group. Therefore, the intraoperative goal-directed fluid therapy appeared to be at lower risk of postoperative AKI than the restrictive regimen, which deserves more larger, higher-quality RCTs to further study [37].…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, our institutional intraoperative monitoring was traditional (static) versus an invasive (dynamic) approach, often used in goal-directed therapy. Nevertheless, a recent meta-analysis found no difference between restrictive fluid management and goal-directed methods 25 . It is also essential to consider that colloid use, especially albumin, has a high amount of sodium chloride, potentially leading to high complication rates, explaining the higher adjusted risk of complications in our study regarding albumin infusion.…”
Section: Discussionmentioning
confidence: 71%
“…Nevertheless, a recent meta-analysis found no difference between restrictive fluid management and goal-directed methods. 25 It is also essential to consider that colloid use, especially albumin, has a high amount of sodium chloride, potentially leading to high complication rates, explaining the higher adjusted risk of complications in our study regarding albumin infusion. As an institutional standard, colloid transfusion is reserved for prolonged operations and given after infusion of higher RL volumes.…”
Section: Discussionmentioning
confidence: 87%
“…A recent article published in the Cochrane database 20 suggests that restrictive fluid therapy is superior to a liberal fluid therapeutic strategy. In a multicenter study, Brandstrup et al 21 investigated a homogenous collective of 172 patients undergoing major colorectal surgery.…”
Section: Discussionmentioning
confidence: 99%